Efektifitas Praktik Penegakan Hukum Perkara Tindak Pidana Korupsi Pasca Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 - Lawalata, Imanuel Jerry Arthur; Picauly, Jessyca Haniel (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this writing is to discuss the Post Constitutional Court Decision Number 25/PUU-XIV/2016 removed the word "may" in the formulation of Article 2 paragraph (1) and Article 3, from the formulation of formal offenses to material offenses, thus causing ineffectiveness for law enforcement officials in handling cases of criminal acts of corruption. The formulation of the problem is how effective law enforcement practices are in handling alleged cases of criminal acts of corruption Article 2 paragraph (1) and Article 3 of the PTPK Law After the Constitutional Court Decision No. 25 / PUU-XIV / 2016. The research method is empirical normative with a descriptive type. Primary data were collected by direct interviews while secondary data were obtained by literature studies which were further analyzed using qualitative methods, as well as using a statutory approach, a conceptual approach. The discussion in this study shows that through Constitutional Court Decision No. 25/PUU-XIV/2016, in practice Often law enforcement is not in line with the ruling. Thus, the Constitutional Court's decision needs to be made in one law because the interpretation of the binding nature of the Constitutional Court's decision is not intended for all parties (erga omnes), but is aimed only at institutions that are given the authority to follow up on the decision of the Constitutional Court, namely the House of Representatives (DPR) or the President as stipulated in Article 10 paragraph (1) letter d and paragraph (2) of Law Number 12 of 2011 concerning the Establishment of Laws and Regulations as amended last time by Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Establishment of Laws and Regulations.